Building a Young Mountain Range: Insight Into the Growth of the Greater Caucasus Mountains From Detrital Zircon (U‐Th)/He Thermochronology and 10Be Erosion Rates. Issue 5 (10th May 2022) - Forte, Adam M.; Gutterman, Kate R.; van Soest, Matthijs C.; Gallagher, Kerry
Abstract: The Greater Caucasus (GC) Mountains within the central Arabia‐Eurasia collision zone are an archetypal example of a young collisional orogen. However, the mechanisms driving rock uplift and forming the topography of the range are controversial, with recent provocative suggestions that uplift of the western GC is strongly influenced by an isostatic response to slab detachment, whereas the eastern half has grown through shortening and crustal thickening. Testing this hypothesis is challenging because records of exhumation rates mostly come from the western GC, where slab detachment may have occurred. To address this data gap, we report 623 new, paired zircon U‐Pb and (U‐Th)/He ages from seven different modern river sediments, spanning a ∼400 km long gap in bedrock thermochronometer data. We synthesize these with prior bedrock thermochronometer data, recent catchment averaged 10 Be cosmogenic exhumation rates, topographic analyses, structural observations, and plate reconstructions to evaluate the mechanisms growing the GC topography. We find no evidence of major differences in rates, timing of onset of cooling, or total amounts of exhumation across the possible slab edge, inconsistent with previous suggestions of heterogeneous drivers for exhumation along‐strike. Comparison of exhumation across timescales highlight a potential acceleration, but one that appears to suggest a consistent northward shift of the locus of more rapid exhumation. Integration of these new datasets with simple models of orogenic growth suggest that the gross topography of the GC is explainable with traditional models of accretion, thickening, and uplift and does not require any additional slab‐related mechanisms. Plain Language Summary: The transition from subduction to building of mountain ranges is a fundamental process shaping the rock record, but our understanding of this process is limited by few well preserved examples. One where this transition is preserved is in the Greater Caucasus Mountains, but the first order drivers of rock uplift and growth of topography remain controversial. Here, it seems the eastern half of the range grew by shortening and thickening of the crust, but uplift of the western half may be driven by removal of a subducted slab. Importantly, direct records of the rate of erosion or exhumation are largely absent in the eastern range. Here we report new data, derived from zircon grains extracted from modern sediments which span the length of the range. Integrating these with prior analyses of cooling rates derived from minerals from in‐situ bedrock samples, we find no meaningful change in the rates at which rocks have uplifted or the total magnitude of rock exhumation along the whole range. Consideration of these new data with records of millennial scale exhumation rates and total amounts of plate motion imply that the evolution of growth of the Greater Caucasus is well explained by shortening and thickening. Key Points: New detrital thermochronology fills 400 km long gap in bedrock data that hindered interpretation of exhumation mechanisms within the Greater Caucasus Synthesis of new and existing thermochronology data imply similar magnitudes and timing of exhumation along‐strike in the Greater Caucasus Comparison of exhumation rates with long‐term estimates of convergence do not require isostatic uplift from slab detachment